Echocardiographic normal reference values and impact of hypertension in a general African population : an echocardiographic study - (:unkn) unknown (My University, 2022)
The impact of non-communicable diseases, particularly cardiovascular diseases, is increasing in sub-Saharan Africa. Our objective was to evaluate from the Beninese longitudinal cohort TAHES the impact of hypertension, from the analysis of 894 echocardiographies. Threshold values for normality of echocardiographic parameters were defined from participants without hypertension, diabetes or obesity. The analysis of this group of normal participants showed a higher ventricular mass with thicker ventricular walls than in the European or American series. The diameters of the proximal and abdominal ascending aorta appeared to be smaller in our population but without modification of the normality thresholds. While only 22% of hypertensive participants were classified as normal by application of aspecific criteria, recategorization with our specific cutoffs showed that 69% of hypertensive participants had normal geometry, 6% ventricular remodeling without hypertrophy, 21% hypertrophy eccentric and 4% concentric hypertrophy. Diastolic dysfunction was present for 14.5% of hypertensive participants. This work confirms the impact of hypertension on left ventricular geometry and diastolic function in sub-Saharan Africa, but also the interest of establishing population-specific norms in order to study the impact of an exposure factor.
Keywords: African Research